Hubungan Coping Stress dan Self-Awareness Dengan Tingkat Kecemasan Pada Anak Binaan Di LPKA Kelas II Palu - Munira R. Kaimudin; Dhevy Puswiartika; Munifah Munifah; Azam Arifyadi (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aimed to determine the relationship between coping stress and self-awareness with anxiety levels among fostered children at LPKA Class II Palu. This research used a quantitative approach with a correlational design. The population consisted of 13 fostered children at LPKA Class II Palu, and the sampling technique used was saturated sampling, in which all members of the population were included as research participants. Data were collected using coping stress, self-awareness, and anxiety scales. Data analysis was conducted using descriptive and inferential statistics assisted by SPSS. The results showed that there was no significant relationship between coping stress and anxiety levels, as well as between self-awareness and anxiety levels among fostered children at LPKA Class II Palu. Simultaneously, coping stress and self-awareness also did not show a significant relationship with anxiety levels. These findings suggest that anxiety among fostered children may be influenced by various factors beyond coping stress and self-awareness, including environmental conditions within the rehabilitation setting, social support, family background, previous life experiences, and other psychosocial factors. Therefore, efforts to understand and address anxiety among fostered children require a broader perspective that considers multiple aspects of their psychosocial development and adjustment.